Community detection in multiplex networks via consensus matrix - Nianwen Ning; Bin Wu (网络与信息安全学报)
In complex network of real world,there are many types of relationships between individuals,and the more effective research ways for this kind of network is to abstract these relationship as a multiplex network.More and more researchers are attracted to be engaged in multiplex network research.A novel framework of community detection of multiplex network based on consensus matrix was presented.Firstly,this framework merges the structure of multiplex network and the information of link between each node into monoplex network.Then,the community structure information of each layer network was obtained through consensus matrix,and the traditional community division algorithm was utilized to carry out community detection of combine networks.The experimental results show that the proposed algorithm can get better performance of community partition in the real network datasets.